Mimicking Behçet's disease: GM-CSF gain of function mutation in a family suffering from a Behçet's disease-like disorder marked by extreme pathergy. (28th January 2021) - Rösler, B; Heinhuis, B; Wang, X; Silvestre, R; Joosten, L A B; Netea, M G; Arts, P; Mantere, T; Lefeber, D J; Hoischen, A; Veerdonk, F L
Summary: Behçet's disease (BD) is an inflammatory disease mainly affecting men along the ancient Silk Route. In the present study we describe a Dutch family suffering from BD-like disease with extreme pathergic responses, but without systemic inflammation. Genetic assessment revealed a combination of the human leukocyte antigen (HLA)-B*51 risk-allele together with a rare heterozygous variant in the CSF2 gene (c.130A>C, p.N44H) encoding for granulocyte–macrophage colony-stimulating factor (GM-CSF) found by whole exome sequencing. We utilized an over-expression vector system in a human hepatocyte cell line to produce the aberrant variant of GM-CSF. Biological activity of the protein was measured by signal transducer and activator of transcription 5 (STAT-5) phosphorylation, a downstream molecule of the GM-CSF receptor, in wild-type peripheral mononuclear cells (PBMCs) using flow cytometry. Increased STAT-5 phosphorylation was observed in response to mutated GM-CSF when compared to the wild-type or recombinant protein. CSF2 p.N44H results in disruption of one of the protein's two N-glycosylation sites. Enzymatically deglycosylated wild-type GM-CSF also enhanced STAT-5 phosphorylation. The patient responded well to anti-tumor necrosis factor (TNF)-α treatment, which may be linked to the capacity of TNF-α to induce GM-CSF in phorbol 12-myristate 13-acetate (PMA)-treated PBMCs, while GM-CSF itself only induced dose-dependent interleukin (IL)-1Ra production. The identified CSF2 pathway could provide novel insights into the pathergic response of BD-like disease and offer new opportunities for personalized treatment. Graphical Abstract: